"It is never too late to fight for one's family and nation": Attempts at "Belarusifying" Soldiers in German-Sponsored Armed Formations, 1941–1944. Issue 2 (2nd April 2020) - Pomiecko, Aleksandra
ABSTRACT: This article explores German-sponsored Belarusian collaborationist armed formations between 1941 and 1944 as pedagogical and educational sites. These groups included the Belarusian auxiliary police, the Belarusian Self-Defense Corps, and the Belarusian Home Guard. Traditionally, such Belarusian armed groups are analyzed in their tactical and operational capacities and particularly in comparison to their Ukrainian or Baltic counterparts. Instead, this article explores how the Belarusian leadership sought to use these groups as educational spaces in an effort to create a 'Belarusian' army. Examining the documentation sheds light as to how the leadership articulated Belarusian identity and what rank-and-file soldiers were exposed to in the non-combative portions of their training.